Assessment of the diagnostic utility of the electroencephalogram in pediatric emergencies - M.J. Abenza Abildúa; T. Olmedo Menchen; A. Pérez Villena; S. Ruhland Paulete; F.J. Navacerrada Barrero; J. de Ojeda Ruíz de Luna; C. Algarra Lucas; G. Cordero Martín; S. Martínez Ubierna; C. Jimeno Montero; I.J. Navarro López; E. Suárez Gisbert; et al. (Neurología (English Edition))
Introduction: We analyze the diagnostic utility of urgent EEG (electroencephalogram) performed in children under 16 years of age in our center. Material and methods: Descriptive, retrospective, observational study of consecutive patients from 0 to 16 years of age, who underwent an urgent EEG for any reason, from January to December 2022. Results: Of the 388 patients, 70 were children: 37 (52.85%) women, and 33 (47.14%) men. Average age: 6.27 ± 4.809. Of the 70 patients, 6 (8.57%) had previous epilepsy. Reasons for consultation: 17 febrile seizures, 10 first focal seizures, 10 first TCG seizures, 6 paroxysmal episodes, 6 absences, 3 myoclonus of extremities, 3 syncope, 2 SE, 2 visual alterations, 2 low level of consciousness, 2 cyanosis, 2 suspected meningitis or encephalitis, 1 choking, 1 atypical headache, 1 chorea, 1 presyncope, 1 language delay. Of the 70 patients, 47 had a normal EEG (67.14%). Of the 47 patients with a normal EEG, 10 were diagnosed with epilepsy, and 3 of them began receiving antiepileptic treatment upon discharge. None of the patients with suspected syncope or paroxysmal disorder (17 patients, 24.28%) had EEG abnormalities. Of the 17 patients with atypical febrile seizures, 3 had EEG abnormalities. Conclusions: A third of the EEG records performed in the Emergency Department showed alterations, probably due to the time taken. Almost half of the patients with suspected epilepsy or EE showed EEG abnormalities, which confirmed the diagnosis in these cases and encouraged the clinician to start drug treatment. No case with a high suspicion of epilepsy was dismissed due to the normality of the EEG recording in our series. No patient diagnosed with syncope or paroxysmal disorder had EEG abnormalities. Nearly a quarter of patients with atypical febrile seizures showed EEG abnormalities. We barely register cases of status epilepticus, probably due to the degree of complexity of our center. Resumen: Introducción: Analizamos la utilidad diagnóstica del EEG urgente realizado en niños menores de 16 años en nuestro centro. Material y métodos: Estudio descriptivo retrospectivo, observacional, de pacientes consecutivos de 0 a 16 años, a los que se ha realizado un EEG urgente de enero a diciembre de 2022. Resultados: De los 388 pacientes, 70 niños: 37 (52,85%) mujeres, y 33 (47,14%) hombres. Edad media: 6,27 ± 4,809. De los 70 pacientes, 6 (8,57%) tenían epilepsia previa. Motivos de consulta: 17 crisis febriles, 10 primeras crisis focales, 10 primeras crisis TCG, 6 episodios paroxísticos, 6 ausencias, 3 mioclonías de extremidades, 3 síncopes, 2 EE, 2 alteraciones visuales, 2 bajo nivel de conciencia, 2 cianosis, 2 sospechas de meningitis o encefalitis, 1 atragantamiento, 1 cefalea atípica, 1 corea, 1 presíncope, 1 retraso del lenguaje. De los 70 pacientes, 47 tuvieron un EEG normal (67,14%). De los 47 pacientes con EEG normal, 10 fueron diagnosticados de epilepsia. Ningún caso de los pacientes con sospecha de síncope o trastorno paroxístico (17 pacientes, 24,28%) tuvo alteraciones en el EEG. De los 17 pacientes con crisis febriles atípicas, 3 tenían alteraciones en EEG. Conclusiones: Un tercio de los registros EEG realizados en Urgencias mostraron alteraciones. Casi la mitad de pacientes con sospecha de epilepsia o EE mostraba anomalías en el EEG, lo que confirmó el diagnóstico en estos casos y favoreció que el clínico iniciara el tratamiento farmacológico. Ningún caso con alta sospecha de epilepsia fue descartado por la normalidad del registro EEG en nuestra serie. Ningún paciente con diagnóstico de síncope o trastorno paroxístico tuvo alteraciones en el EEG. Casi una cuarta parte de los pacientes con crisis febriles atípicas mostraron alteraciones en el EEG.